Structural Characterization of N-Linked Glycans in the Receptor Binding Domain of the SARS-CoV-2 Spike Protein and their Interactions with Human Lectins - Lenza, Maria Pia (2021)
info:eu-repo/grantAgreement/WT/Physiological Sciences/095700 ERC‐2017‐AdG, 788143‐RECGLYCANMR grant 200077 grant RTI2018‐094751‐B‐C21 GC2018‐098996‐B‐I00 RTI2018‐099592‐B‐C22 RTI2018‐101269‐B‐I00 SEV‐2016‐0644 IF/00780/2015 PTDC/BIA‐MIB/31028/2017 UCIBIO UIDB/04378/2020 Infrastructure project 22161 PD/BD/142847/2018